Analisis Pembentukan Tempat Pemeriksaan Imigrasi Dalam Mendukung Kawasan Pariwisata Danau Toba - Jimmi Adi Putra Manurung (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Indonesia is a country that has a wealth of natural resources and natural charm both in waters and land. Therefore, the government prepares a development plan in the tourism sector, namely the National Tourism Strategic Area which aims to increase the source of state and local government revenue so that the existing facilities are built in each tourism destination. Lake Toba is part of the National Tourism Strategic Area, which is expected to become a tourist attraction that brings in domestic and foreign tourists with the support of all areas surrounding Lake Toba, including Raja Sisingamangaraja XII Airport. Foreigners who enter and exit directly through King Sisingamangaraja XII International Airport must go through the Immigration Checkpoint which is the duty and function of immigration. The purpose of the study was to determine and analyze the establishment of an Immigration Checkpoint in supporting tourism in the Lake Toba area with the research location being carried out at Raja Sisingamangaraja XII International Airport. The research used is qualitative/analytical descriptive with a case study approach. Descriptive research is carried out by conducting analytical research studies. Based on the results of research through interviews, observations, documentation, and literature studies, it is known that currently in some ways it can be said that the establishment of airports is good and efficient in carrying out immigration duties and functions. However, there are still some things that need to be improved from technical and facilitative functions, especially during international arrivals so that immigration provides optimal services during immigration checks.